FEATURES OF THE MATERIAL BALANCE CALCULATION OF THREE-PHASE MIXTURES FOR EXTRACTION PROCESSES - Glybin, Vitaliy; Kuznetsova, Olena (Proceedings of National Aviation University, 2018)
Purpose. Improvement of the algorithm for calculating the liquid-liquid-vapor equilibria for binary and ternary mixtures (in application for extraction processes). Methods. Analysis of phase diagrams, modeling of cutting off a part of an equilibrium phase, algebraic transformations of the system of Eqs. describing a single-step evaporation of a three-phase mixture of a given composition. Results. For two types of phase diagrams of binary mixtures with partial miscibility of components in the liquid phase, restrictions on the possible values of the mole fractions of the vapor and two liquid phases under the equilibrium conditions of the liquid-liquid-vapor mixture for a given total composition were obtained. For ternary mixtures, analytical expressions for the calculation of three phases composition for the given two sets of distribution coefficients were obtained. Formulas for calculating mole fractions of vapor and two liquid phases according to the given composition of the mixture are obtained. The following formulas are used to calculate the three-phase equilibrium of the butylene-n-butane-water mixture based on the Raoult’s and Henry’s Laws. Discussion. The obtained formulas can be used to determine approximately the composition of coexisting equilibrium phases of ternary mixtures as well as the mole fractions of phases. For binary mixtures, it is expedient to supplement the input information of the single-step evaporation of a mixture of a given composition with the permissible value of the mole fraction of the vapor phase.